2014
DOI: 10.1177/2151458514525042
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computed Tomography Attenuation to Evaluate Osteoporosis Following Acute Fractures of the Thoracic and Lumbar Vertebra

Abstract: Background: Relatively few patients have dual-energy x-ray absorptiometry to quantify the magnitude of bone loss as they age. Recent work correlates mean computed tomography (CT) attenuation in the level I (L1) vertebra with bone mineral density (BMD), making it possible to objectively evaluate the magnitude of bone loss in osteoporosis by this method. The aims of this study were to evaluate the utility of using CT scans in patients with acute thoracic and lumbar spine fractures to diagnose osteoporosis and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…We have shown that opportunistic CT scans can be employed to evaluate sacral CT attenuation. Prior works show lumbar CT attenuation can predict lumbar BMD, 11,13,14,16,18 and as we have shown that sacral attenuation values correlate strongly with lumbar attenuation values, we therefore infer that sacral CT attenuation values predict sacral BMD. Topographic variations in sacral BMD identified by this method match the relationships found in prior quantitative CT studies.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…We have shown that opportunistic CT scans can be employed to evaluate sacral CT attenuation. Prior works show lumbar CT attenuation can predict lumbar BMD, 11,13,14,16,18 and as we have shown that sacral attenuation values correlate strongly with lumbar attenuation values, we therefore infer that sacral CT attenuation values predict sacral BMD. Topographic variations in sacral BMD identified by this method match the relationships found in prior quantitative CT studies.…”
Section: Resultssupporting
confidence: 73%
“…This study also does not include DXA measurements for evaluation of BMD, instead relying upon previous works which showed correlations between lumbar CT‐attenuation and lumbar BMD as evaluated by DXA. However, prior authors have noted that DXA has limitations, with some theorizing that CT‐based evaluation may be a better measure of true bone mineral density . DXA measures areal BMD (aBMD), which is a 2‐dimensional estimation of the actual 3‐dimensional BMD which can be measured via CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations